2019
DOI: 10.4067/s0717-95022019000100141
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Role of Endoneurial Fibroblast-Like Cells in the Resolution of Endoneurial Oedema Following Nerve Crush Injury

Abstract: Endoneurial oedema is a salient feature of all types of neuropathy. Its elimination is crucial during the complications of nerve recovery. The objective was to study a possible role of the endoneurial fibroblasts in the resolution of nerve edema. Forty-two albino male rats aged between 30 and 40 days (weight 200 g to 250 g) were used in this study. The left sural nerves of 36 rats were subjected to crush injury at one to three-week intervals with six animals per interval. The right and left sural nerves of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Thus, TCs/CD34+SCs have been associated with neuroinflammation in the peripheral nerve [ 103 , 104 ] and with Charcot–Marie–Tooth disease [ 105 , 106 ]. They participate in myelin degradation [ 51 ] and in the resolution or location of endoneurial oedema in the sub-perineurial space following nerve crush injury [ 107 ]. Endoneurial progenitors expressing PDGFRa can participate in heterotopic ossification [ 108 ].…”
Section: Tcs (Tcs/cd34+scs) In the Pathologic Peripheral Nervous Smentioning
confidence: 99%
“…Thus, TCs/CD34+SCs have been associated with neuroinflammation in the peripheral nerve [ 103 , 104 ] and with Charcot–Marie–Tooth disease [ 105 , 106 ]. They participate in myelin degradation [ 51 ] and in the resolution or location of endoneurial oedema in the sub-perineurial space following nerve crush injury [ 107 ]. Endoneurial progenitors expressing PDGFRa can participate in heterotopic ossification [ 108 ].…”
Section: Tcs (Tcs/cd34+scs) In the Pathologic Peripheral Nervous Smentioning
confidence: 99%
“…Many authors were tempted to reevaluate the fibroblasts and fibroblast-like cells. In fact, there are not yet established criteria to discriminate very well the differences between real phenotype of fibroblasts and many other fibroblast-like cell populations [2,80,88,89,94,95]. Moreover, Röyttä et al (1987) appreciated endoneurial fibroblasts as endoneurial fibroblast-like cells [96].…”
Section: Endoneurial Cell Typesmentioning
confidence: 99%
“…The spindle-shaped cells with rectangular or triangular bodies of cells with slender long cytoplasmic processes were described but no assimilation with endoneurial TCs is mentioned. In a recent published study concerning a putative role of endoneurial fibroblast-like cells in the reduction and finally resolution of endoneurial edema after nerve trauma, Elbarrany & Alasmari [94] evaluate that endoneurial fibroblast-like cells might represent around 2-9% of the endoneurial cells. They reported that endoneurial fibroblast-like cells gradually modified their morphology becoming flattened with long-branching cytoplasmic processes and finally form a barrier-like cellular layer, and consequently are involved in localization of endoneurial edema following nerve crush injury.…”
Section: What About the Endoneurial Tcs' Involvement In Nerve Repair ...mentioning
confidence: 99%